Structure of the nucleon's low-lying excitations - Chen, Chen [UNESP]; El-Bennich, Bruno; Roberts, Craig D.; Schmidt, Sebastian M.; Segovia, Jorge; Wan, Shaolong (Amer Physical Soc, 2018)
A continuum approach to the three valence-quark bound-state problem in quantum field theory is used to perform a comparative study of the four lightest (I = 1/2; J(P) = 1/2(+/-)) thorn baryon isospin doublets in order to elucidate their structural similarities and differences. Such analyses predict the presence of nonpointlike, electromagnetically active quark-quark (diquark) correlations within all baryons; and in these doublets, isoscalar-scalar, isovector-pseudovector, isoscalar-pseudoscalar, and vector diquarks can all play a role. In the two lightest (1/2, 1/2(+)) doublets, however, scalar and pseudovector diquarks are overwhelmingly dominant. The associated rest-frame wave functions are largely S-wave in nature; and the first excited state in this 1/2(+) channel has the appearance of a radial excitation of the ground state. The two lightest (1/2, 1/2(-)) doublets fit a different picture: accurate estimates of their masses are obtained by retaining only pseudovector diquarks; in their rest frames, the amplitudes describing their dressed-quark cores contain roughly equal fractions of even-and odd-parity diquarks; and the associated wave functions are predominantly P-wave in nature, but possess measurable S-wave components. Moreover, the first excited state in each negative-parity channel has little of the appearance of a radial excitation. In quantum field theory, all differences between positive-and negative-parity channels must owe to chiral symmetry breaking, which is overwhelmingly dynamical in the light-quark sector. Consequently, experiments that can validate the contrasts drawn herein between the structure of the four lightest (1/2, 1/2(+/-)) thorn doublets will prove valuable in testing links between emergent mass generation and observable phenomena and, plausibly, thereby revealing dynamical features of confinement.